Selected Legal Aspects of Home Office in the Context of the COVID-19 Pandemic - Silvia BARNOVA; Slavka KRASNA (Communications of International Proceedings, 2021)
In the proposed paper, the authors deal with selected aspects of home office in the context of the COVID-19 pandemic. In the Slovak Republic, the current legislation in force distinguishes between home office and telework. Based on the Labour Code as amended, while telework means working from home on a permanent basis, home office is applied occasionally or under specific circumstances in the employee’s household or other specified place with the employer’s consent. The basic precondition is that it is following the employees’ job description and the type of their work. During the first two waves of the pandemic crisis, where it was possible, home office was applied.  As given by the COVID Automat and its alert system, in the so-called red regions – based on a government regulation and the directive of the Chief Hygienist – employers did not even have a choice, they could not decide between allowing or not allowing home office if there was not any real barrier to performing a particular type of work from home. It means that during the state of emergency, employers were obliged to order home-office for their employees and a need for changes in legislation has arisen. The purpose of the paper is to introduce new regulations in the field of home office in the context of the COVID-19 pandemics.
Keywords: Home office; telework Labour Code; Amendment; COVID-19